Effectiveness of peer-led education intervention on contraceptive use, unmet need and demand among secondary school adolescents in Gedeo Zone, South Ethiopia. A study protocol for cluster randomized controlled trial - Yohannes Addisu Wondimagegene; Gurmesa Tura Debelew; Zewdie Birhanu Koricha (Clinical Epidemiology and Global Health, 2023)
Background: School-based interventions are believed to increase contraceptive use and demand among adolescents. However, there is limited evidence on the effectiveness of peer education in promoting contraceptive use, unmet needs, and demand among adolescents aged 15–19 years. Objective: The purpose of this study protocol will be to evaluate the effect of a peer-led educational intervention on increasing contraceptive use and demand among high school students in the Gedeo Zone of southern Ethiopia. Methods: A single-blind randomized controlled trial will be conducted in 6 randomly selected secondary schools in the Gedeo zone of southern Ethiopia. Two hundred twenty-four participants will be selected and randomly assigned to two groups: an intervention group and a control group. A peer-led educational intervention will be administered to the intervention group for six months. Pre-tested and validated questionnaires will be used to measure contraceptive use, unmet need and contraceptive demand. Generalized estimating equation (GEE) will be used to test the effectiveness of the interventions by examining whether there is any significant difference in contraceptive use, unmet needs, and contraceptive demands between the intervention and control groups. Trial registration: This trail was registered under Clinical Trials.gov with identifier number PACTR202109586981531.